The Role of International Amnesty in China's Discrimination Conflict Against Uyghur Muslims in Xinjiang 2018-2022 - Al-Asad, Havez; Zarkachi, Imam (Mediasi Journal of International Relations, 2023)
One of the internal conflicts that occurred in the Chinese government was the human rights violations that occurred against ethnic Uyghur Muslims in Xinjiang. Violations committed by the Chinese government include forced imprisonment, prohibition of freedom of religion, forced marriage and sexual harassment of women. Therefore, Amnesty International as a non-governmental organization that aims to promote and uphold human rights throughout the world, one of its roles is to protect the Uyghurs in Xinjiang. Amnesty International has played a role in addressing the Uyghur problem by taking action to interview victims of forced incitement by the Chinese government conducting several campaigns to lead public opinion about discrimination that occurs in China, and emphasizing the Chinese government that aims to reduce discrimination there and working with the world and international organizations to urge the Chinese government to reduce and minimize violence that occurs.